Literature Review: Peran Salmon Ovary Peptide pada Tata Laksana Komprehensif - Febri Endra Budi Setyawan; Laili Purnamasari; Mohammad Kuntadi Syamsul Hidayat (ARTERI : Jurnal Ilmu Kesehatan, 2023)
Salmon ovary peptide (SOP) is an additional preparation derived from the main ingredient in the form of eggs or salmon caviar resulting from an extraction process with a mixture of peptides. Salmon contains various nutrients including B vitamins, vitamin D, niacin, phosphorus, high protein and also high in omega 3 fatty acids. This study aims to study the benefits of salmon eggs against various health problems. The method used is a literature review based on articles that have been published in national and international journals published the longest in the last 10 years. One of the best sources of long-chain omega-3 fatty acids EPA and DHA is salmon. Farmed salmon has 2.3 grams of long-chain omega-3 fatty acids per 100 grams, while wild salmon contains 2.6 grams/100 grams. Salmon ovary peptide contains benefits including: 1) Reducing the risk of heart disease; 2) Supports fetal development; 3) Reducing inflammation; 4) Helps overcome depression; 5) Improve brain health; 6) Maintain eye health; 7) Lowering high blood pressure; and 8) Prevent skin damage.